2014
DOI: 10.1016/j.rmed.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery size as a predictor of pulmonary hypertension and outcomes in patients with chronic obstructive pulmonary disease

Abstract: The PA:A ratio is associated with underlying pulmonary hypertension in patients with COPD and is an independent predictor of mortality. This readily available measurement may be a valuable non-invasive screening tool for underlying pulmonary hypertension in COPD patients and appears to impart important independent prognostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
83
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 26 publications
11
83
0
Order By: Relevance
“…Specifically, it is well established that pulmonary hypertension is associated with worse outcomes in IPF, which may explain our observations [20]. Furthermore, prior studies have shown an association between PA:A ratio >1 with COPD exacerbations and worsened outcomes [15,16]. Whether or not the same relationship between exacerbations and pulmonary artery size holds true in IPF requires exploration in future studies.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Specifically, it is well established that pulmonary hypertension is associated with worse outcomes in IPF, which may explain our observations [20]. Furthermore, prior studies have shown an association between PA:A ratio >1 with COPD exacerbations and worsened outcomes [15,16]. Whether or not the same relationship between exacerbations and pulmonary artery size holds true in IPF requires exploration in future studies.…”
Section: Discussionmentioning
confidence: 75%
“…Indeed, the association between pulmonary artery size and prevalent pulmonary hypertension in fibrotic lung disease has yielded mixed results [11][12][13][14]. However, the association between pulmonary artery dilation on CT and clinical outcomes in IPF has, to the best of our knowledge, not been assessed, while recent studies in chronic obstructive pulmonary disease (COPD) have demonstrated the ability of the ratio of the pulmonary artery to the aorta to predict exacerbations and mortality [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…First, it was a single-center retrospective analysis and is thus subject to the usual shortcomings of these types of studies; our observations, however, are mechanistically and physiologically sound and compatible with our earlier report as well as others linking the PA/A ratio and COPD-related pathophysiology. 17,18,47 In addition, our sample size was relatively small, limiting our ability to detect statistical differences in some of the observed trends in clinical outcomes. Another limitation is that we did not evaluate the impact of pharmacologic therapies on clinical outcomes.…”
Section: 46mentioning
confidence: 99%
“…ON development of COPD, pulmonary vessels changed with the destruction of vascular bed and pulmonary vascular remodeling, causing PH. 19 This study was thus undertaken to identify the association of MPA/AAo ratio and pulmonary hypertension by CT chest.…”
Section: -15mentioning
confidence: 99%